The Influence of Electronic Medical Record Implementation on Medical Staff Performance at NTB Provincial Hospital: The Moderating Role of Leadership and Organizational Culture - Rasio, Renty Diana; Nururly, Santi; Wahyulina, Sri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of Electronic Medical Records (EMR) implementation on the performance of medical personnel at the Regional General Hospital of West Nusa Tenggara Province, with leadership and organizational culture as moderating variables. The research employs a quantitative associative–causal design using proportional random sampling, involving 93 respondents comprising physicians, nurses, and medical record officers. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that EMR implementation has a positive and significant effect on employee performance (β = 0.245, t = 2.318, p = 0.021). Furthermore, leadership (β = 0.151, t = 2.123, p = 0.034) and organizational culture (β = 0.158, t = 2.068, p = 0.039) significantly moderate this relationship, thereby strengthening the influence of EMR implementation on employee performance. The research model demonstrates substantial explanatory power with an R² value of 0.878, indicating that 87.8% of the variability in employee performance is explained by EMR implementation, leadership, and organizational culture. These findings underscore that effective leadership enhances employee motivation and digital readiness, while an adaptive organizational culture fosters collaboration, accuracy, and innovation in clinical practice.